Application of Empty Fruit Bunches Compost and Types of P Fertilizer on the Growth and Phosphorus Uptake in Oil Palm Seedlings - Pauliz Budi Hastuti; Sri Manu Rohmiyati (Agrotechnology Research Journal, 2020)
This research aimed to evaluate the effect of empty fruit bunches (efb) compost, phosphate-solubilizing bacteria (PSB), lime, and types of P fertilizer on the growth and availability of Phosphorus and P uptake in the pre-nursery (PN) oil palm seedlings in latosols. The pot experiments were arranged in a Factorial Completely Randomized method. The first factor was the application of efb compost: without efb compost, efb compost, without efb compost + PSB, and without efb compost + lime. The second factor was the types of P fertilizer: SP-36, RP, guano, and NPKMg + Urea as a control. The results showed that the combination of without efb compost +lime and RP fertilizer produces the highest number of leaves. The influence of a single factor showed that the application of without efb, efb compost, without efb compost +PSB, without efb compost + lime, resulted in the same growth of seedlings, except on plant height and the length of the leaf. The various types of P fertilizer led to the same growth of seedlings except for stem diameter. The highest available P was obtained in the combination of without efb compost + PSB with SP-36 fertilizer, which was 631.1% compared to control (without efb compost and NPKMg, Urea) and the lowest in the combination of without efb compost + lime with (NPKMg, Urea). The treatment without efb compost + lime with SP-36 fertilizer increased P uptake of leaves by 55.6% and stem by 47.1% compared to control.